Dynamic Interactions between Commuters’ Mode Choice Behaviour and Integrated Traveller Information - Meng, Meng; Memon, Abdul Ahad; Wong, Yiik Diew; Lam, Soi Hoi (Promet - Traffic&Transportation, 2015)
A commuter’s mode choice decision in response to provided traveller information is directly dependent on the temporal and spatial interactions between the available travel modes, the network performance and control schemes, and the supplied traveller information. A self-developed simulation model – Intelligent Network Simulation Model (INSIM) – was employed to simulate travel scenarios in a multimodal transportation network. A set of experiments was designed to analyse and evaluate the influence of traffic information on commuter’s mode choice, using a medium-sized area in Singapore. Simulation results showed that the private-to-public mode switch propensity bears a strong and direct relation with amount of disseminated integrated multimodal traveller information (IMTI) as well as timeliness of information update. Other influential factors include degrees of accessibility and compliance to IMTI, and congestion-related events such as accidents.